Finite element study of trochanteric gamma nail for trochanteric fracture - K. Sitthiseripratip (2018)
A three-dimensional finite element study of trochanteric fracture fixation by a trochanteric gamma nail (TGN) was investigated in this study. The analyses were performed under one-legged stance load boundary conditions to study the stress distribution and displacements. The influence of material properties (E-modulus) of the implant, the bone and contact condition in the fracture zone was determined. The results show that the stresses in the implant were lower in case of titanium alloy implant material but at the same time higher displacements occurred. The results also indicate that the stresses in the TGN gradually reduced throughout the healing process of the bone in the fracture zone. © 2003 IPEM. Published by Elsevier Science Ltd. All rights reserved.